Organizational Commitment and Fraud Awareness on Fraud Prevention, with Forensic Accounting Skills as a Moderating Variable - Mario Zulfa Nasution; Etty Murwaningsari; Sekar Mayangsari; Mazzlida Mat Deli (Institut Bisnis dan Informatika Kesatuan, 2026)
Fraud remains a critical challenge in public sector governance, requiring effective preventive strategies. This study examines the effects of organizational commitment and fraud awareness on fraud prevention, as well as the moderating role of forensic accounting skills in strengthening these relationships among the Government Internal Supervisory Apparatus (APIP). Using a quantitative approach, primary data were collected through questionnaires and interviews from 450 APIP officers across 32 Indonesian ministries and state institutions selected via purposive sampling. The data were analyzed using SPSS. The results indicate that fraud awareness has a significant positive effect on fraud prevention, while organizational commitment does not. Forensic accounting skills do not moderate the relationships between organizational commitment or fraud awareness and fraud prevention, but they have a significant direct effect. Additionally, internal control systems and risk management positively contribute to fraud prevention. These findings suggest that public sector fraud prevention should focus on strengthening fraud awareness through continuous education and an integrity-based culture, while integrating prevention efforts with internal control and risk management systems. Moreover, forensic accounting skills should be positioned as proactive components of fraud prevention frameworks, not merely investigative tools.